Network economy or just a new breed of multinationals? relocation of eWork as a window to the restructuring of value chains. (1st July 2007) - Jörg Flecker
Abstract : The global information economy is subject to processes of profound restructuring based on new information and communication technologies. These processes follow different logics, with centralisation within international companies playing as significant a role as decentralisation or the development of networks. This paper makes use of findings from the EMERGENCE and Asian EMERGENCE case study research into telemediated work and relocation of work to shed light on the restructuring of global companies, the dynamics of boundaries between corporations and the emerging new international division of labour in the information economy.